(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
The regularities of formation of surfactant-rich phases from the solutions of sodium dodecylsulphate at the presence of cationic polyelectrolyte polyhexamethylenguanidine chloride were investigated. The influence of polyacrylic acid, gelatin, nonionic surfactant OP-7 and other hydrotropic additions on the conditions of surfactant-rich phase formation was studied. The optimal concentration and temperature conditions for the preconcentrating of the microcomponents by surfactant-rich phases were found.